The Evolution of Galaxies in Proto-clusters - Werner, Stephane V. (2023)
In this thesis, I report on my work on galaxy evolution in proto-clusters. In Chapter 1, I describe previous knowledge about clusters and proto-clusters of galaxies. The next three Chapters correspond to three different projects I have completed during my PhD that are connected to the topic of galaxy evolution in proto-clusters.